Komunikasi Digital Dalam Produksi Konten “Kamus Politik” Tiktok @cnnindonesia - Anhar, Nazhea Rachel Ainayya; Dirgantara, Pradipta (eProceedings of Management, 2024)
The creation of this project is underpinned by the rapid advancements in technology witnessed in recent years, notablyin computers, the internet, and mobile devices, reshaping our lifestyles, professions, and social interactions, andembedding digital communication as an indispensable component across various spheres of life. The primaryobjective of this endeavor is to delve into the realm of digital communication within the context of producing contentfor CNN Indonesia's